Nilai kekerasan permukaan pada beberapa tipe beton dengan agregat buatan dan korelasinya terhadap kuat tekan - N.N. Kencanawati; H. Hariyadi; N. Ngudiyono; B. Anshari; L.G.A. Mukti (Universitas Mataram, 2024)
Along with the development of technology to utilize waste in order to create sustainable concrete materials; therefore, this research tries to apply several artificial aggregates derived from concrete waste and fly ash. The test object was a standard concrete cylinder measuring 150 mm in diameter and 300 mm in height. Concrete was made from geopolymer coarse aggregate, treated recycled coarse aggregate, and conventional coarse aggregate. The surface hardness value was measured using a hammer test to obtain the rebound number (RN). Tests were also conducted on concrete with natural aggregate. The results show that the RN value of treated recycled coarse aggregate concrete is in the second place after normal aggregate concrete, followed by the RN value of conventional recycled coarse aggregate. Concrete with geopolymer coarse aggregate is concluded to be lightweight low strength concrete based on the RN value and compressive strength obtained. Furthermore, the relationship between RN values and compressive strength for other concretes is shown by the correlation of y = 0.837 x + 3.627, where y is the concrete compressive strength (MPa) and x is the surface hardness value (RN).